PENGARUH CLIENT IMPORTANCE DAN PERGANTIAN AUDITOR TERHADAP KUALITAS AUDIT - Atik R, Tri Wahyuni (Jurnal Akuntansi AKUNESA, 2014)
This study examined the effect of client importance and auditor changes on audit quality. Audit quality is proxied by total accrual of the company. Method use is multiple linear berganda. This study uses secondary data from companies that listing on the Indonesia Stock Exchange for the period 2009-2011. The results of statistical tests using multiple linear regression, there are evidences that client importance significant effect on audit quality,while auditor turnover no significant effect on audit quality. There are several reason why rotation (audit turnover) did not effect audit quality, caused by the reluctance of market participants to explore further whether the auditor who issued the opininon on the audited financial statements had actually experienced the rotation or not. Basically the market in Indonesia was largely considered capital again, so it is less likely to use fundamental analysis (financial report) for consideration by taking action to sell or buy shares.Keywords: Client Importance, Auditor Turnover and Quality Audit